Im/Materiality in Renaissance Arts - Kate van Orden; Lisa Pon (Arts, 2024)
The inspiration for this Special Issue on Im/Materiality in Renaissance Arts arose from two convictions: (1) that sensual experiences and the physicality of creation must be a part of our accounts of the past, and (2) that crosstalk among scholars of music, literature, art, and architecture can reveal both the historiographical gaps endemic to specific disciplines and the critical tools each specialty brings to the project of incorporating living, breathing artists, builders, poets, singers, players, worshippers, scientists, and others into histories of the Renaissance arts [...]